Hubungan Stigma Masyarakat dengan Sikap Masyarakat derhadap Orang dengan Gangguan Jiwa di Desa Cot Rumpun Kabupaten Aceh Besar - Hayatul Firda; Khaira Rizki; M. Daud (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Although often overlooked by society, mental health is a crucial component of overall health. One of the biggest barriers to managing mental health is the societal stigma associated with People with Mental Disorders (ODGJ). High stigma can lead to negative perceptions that hinder the healing process of those suffering from mental illness. The purpose of this study was to determine how societal perceptions of individuals with mental illness in Cot Rumpun Village, Aceh Besar Regency, relate to societal stigma. This study used a cross-sectional methodology and a descriptive analysis design. Seventy respondents were selected for the study sample using a direct random selection method. The Community Attitudes Against Mentally Ill (CAMI) questionnaire measured public sentiment, and the Perception of Discrimination and Devaluation (PDD) questionnaire measured stigma. Chi-square tests were used in univariate and bivariate data analysis. The majority of respondents expressed positive attitudes toward those with mental health problems (60.0%), while low stigma toward those with mental disorders (54.3%). The results of the Chi-Square test indicate a significant relationship between community stigma and community attitudes towards people with mental disorders (ODGJ) with a value of ρ = 0.000 (ρ <0.05). Health workers are expected to conduct routine counseling and psychoeducation to the community about mental health, including how to deal with, support people with mental disorders appropriately, reducing stigma in the community environment. Local governments and community leaders are also expected to play an active role in creating an inclusive, supportive, discrimination-free social environment for people with mental disorders (ODGJ).